Primeiras manifestações de identidade de gênero: um estudo com crianças de 16 a 18 meses - Pascoto, Renata (2006)
Human sexuality is a theme that awakes interest of the society as a whole, by raising curiosity, anticipation, besides being one more determinant of every individual s personality formation. Former studies have suggested that, far before age three, children start to categorize objects and express gender-based preference, that is, they tend to choose objects which, according to their culture, are appropriate to their biological sex. This research deals with the early manifestations of gender identity. It aims at investigating whether young children´s behavior is associated to their sexual categories: male and female. 20 children have taken part of the experiment: 10 girls and 10 boys between 16 and 18 months of age coming from middle-low income households. The children have been filmed in the presence of toys considered to be adequate either to female or male gender. Their preferential choices and toy handling period has been assessed. The results have showed that since 16 to 18 months of age, boys and girls make different choices based on the Male/Female dichotomy, and express preference for toys which are regarded in their culture as suitable to the sexual category to which they belong